2022
DOI: 10.1177/27526461211068518
|View full text |Cite
|
Sign up to set email alerts
|

Transgender and non-binary students’ experiences at UK universities: A rapid evidence assessment

Abstract: UK universities often position themselves as inclusive institutions that celebrate diversity. As the number of transgender and non-binary (TNB) students at Higher Education Institutes (HEI) rises, universities may seek to improve their campus and online environments so that they are inclusive for all. A Rapid Evidence Assessment (REA) was conducted to explore the experiences of TNB students at UK universities. Drawing on 15 sources (5 fully reviewed papers and 10 supporting citations), the REA identified commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For lesbian, gay, bisexual, trans and sexually/ gender diverse (LGBTQ+) individuals in academia, added pressures, discrimination and peers' lack of knowledge about LGBT + issues still exist (Smith et al, 2022). The decision to 'come out' at work and disclose their identity can be incredibly difficult and stressful to take, and for those that do, there is the high probability of tokenism, where they are expected to represent the LGBTQ + community in various ways (Prock et al, 2019).…”
Section: Inequalities In Uk Higher Education Institutionsmentioning
confidence: 99%
“…For lesbian, gay, bisexual, trans and sexually/ gender diverse (LGBTQ+) individuals in academia, added pressures, discrimination and peers' lack of knowledge about LGBT + issues still exist (Smith et al, 2022). The decision to 'come out' at work and disclose their identity can be incredibly difficult and stressful to take, and for those that do, there is the high probability of tokenism, where they are expected to represent the LGBTQ + community in various ways (Prock et al, 2019).…”
Section: Inequalities In Uk Higher Education Institutionsmentioning
confidence: 99%
“…2 In the UK, it was found that verbal harassment was more prevalent than physical violence towards LGBTI+ individuals which nevertheless creates a 'climate of fear' (Ellis 2009: 727) and places them at increased risk of psychological distress. Other studies demonstrated that discrimination leads to isolation and avoidance of campus and other students with perpetrators being fellow students from LGBTI+ community (Evans et al 2017;Papadaki 2017;Smith et al 2022;Campen et al 2022). Victims of homo-, bi-or trans-phobic bullying report higher levels of stress and anxiety, lower self-esteem and poorer academic achievements as well as long-term academic success (Maunder, Crafter 2018; Young-Jones et al 2015, as quoted in Clark et al 2022: 1).…”
Section: Introductionmentioning
confidence: 99%